Clinical Actionability of Molecular Targets in Endometrial Cancer - Urick, Mary Ellen (Nat Rev Cancer, 2019)
Endometrial cancer accounts for ~76,000 deaths amongst women worldwide. Disease mortality and the increasing number of new diagnoses make endometrial cancer an important consideration in women’s health, particularly in industrialized countries, where the incidence of this tumor type is highest. Most endometrial cancers are carcinomas, with the remainder being sarcomas. Endometrial carcinomas can be classified into several histological subtypes including endometrioid, serous and clear cell carcinomas. Histological subtyping is currently routinely used to guide prognosis and treatment decisions for endometrial cancer patients, while ongoing studies are evaluating the potential clinical utility of molecular subtyping. In this review we summarize the over-arching molecular features of endometrial cancers and highlight recent studies assessing the potential clinical utility of specific molecular features for early detection, disease risk stratification, and directing the use of targeted therapies.